Optimization of Pesticide Analysis Method for Diazinon and Chlorantraniliprol Using High Performance Liquid Chromatography (HPLC) - Marselina Theresia Djue Tea; Akhmad Sabarudin; Hermin Sulistyarti (Natural B, Journal of Health and Environmental Sciences, 2017)
Methods of obtaining diazinone and chlorantraniliprol in soil samples have been developed. Analytes were extracted using acetonitrile by using an ultrasonic solvent extraction method (USE). The discovery uses high performance liquid chromatography using a UV detector. The optimum conditions for the separation of both pesticides are Acetonitrile composition: Air (60:40), flow rate 0.4 mL / min, and at 220 nm wavelength. The more the amount of acetonitrile in the eluent mixture the faster the retention time in the column. Retention time respectively, chlorantraniliprol 10,525, and diazinon 21,029.